A Review on Novel Microstrip Patch Antenna Designs and Feeding Techniques - Christina, G. (IRO Journal on Sustainable Wireless Systems, 2022)
Mobile technology is rapidly advancing nowadays due to its high impact in our day-to-day lives. As a result, there is an increasing need to study the advancement of antenna systems, which are regarded as fundamental equipment for wireless connectivity. Compared to the traditional large size antennas, microstrip patch antennas are now widely used in different applications such as smart phones, military, smart wearable devices etc. due to its unique characteristics such as lighter weight, reconfigurable structure, foldability, ease of fabrication, multi-frequency operations, and compactness. This research study presents a review on various microstrip patch antenna designs and the different antenna feed mechanisms available for 5G applications.
Keywords: Compact antenna design; microstrip antenna; antenna feed mechanisms; multi-frequency band antenna